Alterations of Gut Microbiota in Cholestatic Infants and Their Correlation With Hepatic Function - Guo, Cheng; Li, Yinhu; Wang, Peipei; Li, Yingchao; Qiu, Chuangzhao; Li, Muxia; Wang, Daxi; Zhao, Ruiqin; Li, Dongfang; Wang, Ye; Li, Shuaicheng; Dai, Wenkui; et al. (Frontiers in Microbiology, 2018)
Cholestasis is a major hepatic disease in infants, with increasing morbidity in recent years. Accumulating evidence has revealed that the gut microbiota (GM) is associated with liver diseases, such as nonalcoholic steatohepatitis, cirrhosis, and hepatocellular carcinoma. However, GM alterations in cholestatic infants and the correlation between GM and hepatic functions remain uninvestigated. In this study, 43 cholestatic infants (IC group) and 37 healthy infants (H group) were enrolled to detect GM discrepancies using 16S rDNA analysis. The diversity in the bacterial community was significantly lower in the IC group than that in the H group (P=0.013). After determining the top 10 abundant genera of microbes in the IC and H groups, we found that 13 of them were differentially enriched, including Bifidobacterium, Bacteroides, Streptococcus, Enterococcus, and Staphylococcus. As compared with the H group, the IC group had a more complex GM co-occurrence network featured by 3 core nodes: Phyllobacterium, Ruminococcus, and Anaerostipes. In addition, the positive correlation between Faecalibacterium and Erysipelatoclostridium (r=0.689, P=0.000, FDR=0.009) was not seen in IC patients. Using the GM composition, cholestatic patients can be distinguished from healthy infants with high accuracy (areas under receiver operating curve (AUC)>0.97), wherein Rothia, Eggerthella, Phyllobacterium, and Blautia identified as valuable biomarkers. Using KEGG annotation, we identified 32 functional categories with significant difference in enrichment of the GM of IC patients, including IC-enriched functional categories that were related with lipid metabolism, biodegradation and metabolism of xenobiotics, and various diseases. In contrast, the number of functions associated with amino acid metabolism, nucleotide metabolism, and vitamins metabolism were reduced in IC patients. We also identified significant correlation between GM composition and indicators of hepatic function. Megasphaera positively correlated with total bilirubin (r=0.455, P=0.002) and direct bilirubin (r=0.441, P=0.003), whereas γ-glutamyl transpeptidase was positively associated with Parasutterella (r=0.466, P=0.002) and negatively related with Streptococcus (r=-0.450, P=0.003). This study describes the GM characteristics in cholestatic infants, illustrates the association between GM components and hepatic function, and provides solid theoretical basis for GM intervention for the treatment of infantile cholestasis.